2019
DOI: 10.1016/j.fertnstert.2019.07.273
|View full text |Cite
|
Sign up to set email alerts
|

In vitro fertilization with personalized blastocyst transfer versus frozen or fresh blastocyst transfer: a multicenter, randomized clinical trial

Abstract: EBL). Spearman's correlation was used to evaluate the correlation between leiomyomata volume and operative outcomes. Receiver-operator-characteristic (ROC) curves were constructed for outcomes showing statistical significance.RESULTS: A total of 117 patients were included; there was no difference in the demographics or leiomyomata characteristics of patients undergoing MRI or US in the AM (n¼69), LM (n¼13) or RALM (n¼35) groups. The mean age and leiomyomata volume of patients undergoing LM was 36.7AE7.1 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 0 publications
1
9
0
2
Order By: Relevance
“…A total of 75% of our patient's ERA results showed that endometrium was found to be receptive which is comparable with the study of Patel et al 7 ERA helps finding out a personalized WOI for majority of these patients with previous implantation failure. In addition, the results of positive beta HCG in our 12 patients, as a marker of receptivity, are comparable to the study of Simon et al 12 and Mahajan et al 16 ERA test is accurate and sensitive in identifying genetic expressions of the endometrium to pinpoint embryo transfer timing. 19,20 PET guided by ERA significantly improves pregnancy rates in patients with unexplained repeated implantation failure.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…A total of 75% of our patient's ERA results showed that endometrium was found to be receptive which is comparable with the study of Patel et al 7 ERA helps finding out a personalized WOI for majority of these patients with previous implantation failure. In addition, the results of positive beta HCG in our 12 patients, as a marker of receptivity, are comparable to the study of Simon et al 12 and Mahajan et al 16 ERA test is accurate and sensitive in identifying genetic expressions of the endometrium to pinpoint embryo transfer timing. 19,20 PET guided by ERA significantly improves pregnancy rates in patients with unexplained repeated implantation failure.…”
Section: Discussionsupporting
confidence: 88%
“…Total RNA is obtained from endometrial biopsy and used for genomic expression to check receptivity. 12 ERA evaluates 238 genes expressed during WOI using RNA sequencing. 13 Following analysis, endometrium is classified as receptive or nonreceptive (NR).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, we suggested that blinding of participants in this circumstance was not applicable. When excluding the blinding criteria as in Figures 4 and 5 (11,16,26,27), the 2 studies of Simon et al (11,26) achieved a moderate level of quality. However, the remaining 2 RCTs still had a high risk of bias because of the incomplete data outcomes and lack of selective reporting (16,27).…”
Section: Quality Assessment Of the Selected Studiesmentioning
confidence: 98%
“…The detailed characteristics of the included studies, such as the study design, country, year, patient characteristic, sample size, mean age, and primary outcome, are shown in Table 1 (26)(27)(28)(29)(30)(31)(32)(33). In general, the 17 studies (4 RCTs and 13 cohort studies) included data from 7,052 patients who underwent PET and standard embryo transfer (SET).…”
Section: Description Of the Selected Studiesmentioning
confidence: 99%
See 1 more Smart Citation